2018
DOI: 10.1177/0194599818777240
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Body Mass Index on Operative Outcomes in Head and Neck Free Flap Surgery

Abstract: Obesity does not increase the risk for postoperative complications in head and neck free flap surgery and may be protective in some cases. When assessing a patient's fitness for surgery, underweight status or recent weight loss may suggest a reduced ability to tolerate extensive free flap reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
48
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 27 publications
3
48
2
Order By: Relevance
“…In the present study, any preoperative weight loss had a statistically significant association with severe surgical complications, whereas the WHO's definition of underweight did not. Reporting weight loss as a stronger predictor of complications than underweight has been shown in some published studies [23], whereas others do not confirm this [17,24]. Interestingly, stratified analysis among patients with obesity (BMI 30 kg/m 2 ) in the current study population demonstrated that weight loss increased the risk of severe surgical complications also in this group.…”
Section: Discussioncontrasting
confidence: 56%
“…In the present study, any preoperative weight loss had a statistically significant association with severe surgical complications, whereas the WHO's definition of underweight did not. Reporting weight loss as a stronger predictor of complications than underweight has been shown in some published studies [23], whereas others do not confirm this [17,24]. Interestingly, stratified analysis among patients with obesity (BMI 30 kg/m 2 ) in the current study population demonstrated that weight loss increased the risk of severe surgical complications also in this group.…”
Section: Discussioncontrasting
confidence: 56%
“…37 Consistent with our findings, studies utilizing BMI as an anthropometric measure to predict surgical outcomes in head and neck free flaps have concluded that BMI does not significantly influence postoperative outcomes in these patients. 38 A recent study by Crippen et al analyzed the impact of BMI on head and neck free flap surgery outcomes by evaluating medical and surgical complications in 2,187 patients from the NSQIP database. The study concluded that BMI does not significantly influence postoperative outcomes, similar to findings reported by Hyun et al 39 Thus, it is important to understand that BMI and SMI are distinct anthropometric measures without a strong correlation as demonstrated by our study (►Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recent nationwide analyses evaluating all modalities of microvascular H&N reconstruction have identified factors that are associated with postoperative complications, including anesthesia duration, low preoperative body weight, a longer length of postoperative hospital stay, age, and smoking status (Brady et al, 2018; Cannady et al, 2017; Crippen et al, 2018; White et al, 2015). However, these studies do not isolate outcomes of microvascular osseous reconstruction, nor do they parse out the comparative outcomes of BBFs and OCFs.…”
Section: Introductionmentioning
confidence: 99%
“…The most common types of osteocutaneous free flaps are harvested from the radial forearm, scapula, and fibula (Hanasono, Matros, & Disa, 2014). (Brady et al, 2018;Cannady et al, 2017;Crippen et al, 2018;White et al, 2015). However, these studies do not isolate outcomes of microvascular osseous reconstruction, nor do they parse out the comparative outcomes of BBFs and OCFs.…”
mentioning
confidence: 99%